Brazilian and Chinese Cooperation in African Agriculture. A Practice-based Study - Frédéric Goulet; Jean-Jacques Gabas; Eric Sabourin (Íconos)
In this article we analyze Brazilian and Chinese practices in terms of cooperation in Africa, focusing on the agricultural sector. While a great deal of work has analyzed the engagement of these emerging players from an international relations viewpoint, we develop a practice based analysis, involving the ethnographic observation of cooperation projects and institutions. Firstly we show that, although justification rhetoric insists on a break with post-colonial and “economically motivated” cooperation, the national programs of China and Brazil are closely linked to commercial and industrial interests. Secondly we show, particularly for Brazil, that the professionalization of cooperation activities remains a major challenge for South-South cooperation.